Highly Efficient Low‐Frequency Broadband Sound Absorption with a Composite Hybrid Metasurface. Issue 10 (21st October 2021) - Liang, Qingxuan; Wu, Yutao; Lv, Peiyao; He, Jin; Ma, Fuyin; Chen, Tianning
Abstract : A highly efficient low‐frequency broadband sound‐absorbing metasurface, which is composed of a perforated panel and coiled‐up cavities with separating plates, is successfully realized as described in article number 2100791 by Qingxuan Liang and co‐workers. Compared with the traditional sound absorbing materials, the composite hybrid honeycomb metasurface can achieve an excellent absorption and mechanical performance simultaneously with a simple and stable structure for practical application of low‐frequency noise control.